2021
DOI: 10.1021/acs.inorgchem.1c02600
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Information in the L3 X-ray Absorption Spectra of Molybdenum Compounds by High-Energy-Resolution Detection and Density Functional Theory

Abstract: X-ray spectroscopy using high-energy-resolution fluorescence detection (HERFD) has critically increased the information content in X-ray spectra. We extend this technique to the tender X-ray range and present a study at the L3-edge of molybdenum. We show how information on the oxidation state, phase composition, and local environment in molybdenum-based compounds can be obtained by analyzing the HERFD L3 X-ray absorption near-edge structure (XANES). We demonstrate that the chemical shift of the L3-edge HERFD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Figure shows XANES measurements of the Mo-L 3 edges of LiMo 8 O 10 and a series of oxide standards with differing valances/configurations: MoO 3 (Mo 6+ , d 0 ), SrFe 0.5 Mo 0.5 O 3 (Mo 5+ , d 1 ), Sm 2 Mo 2 O 7 (Mo 4+ , d 2 ), MoO 2 (Mo 4+ , d 2 ), and elemental Mo (Mo 0 , d 5 ). The intense near-edge “white line” (WL) features in the spectra are due to dipole transitions from the 2p core level into empty 4d final states. The characteristic chemical shift of the absorption edge to higher energy with increasing valence can be seen in Figure by the systematic shift to the higher energy of the centrum of the WL feature with increasing Mo-valence. The loss of screening (an increase of binding energy) with increasing valence is typically invoked for such chemical shift trends . The strong splitting of the oxide spectra due to ligand field and band structure effects can complicate the evaluation of the WL chemical shift. The first moment of the near edge, E M , as defined in eq , has been used to estimate the relative chemical shifts of XANES spectra with strong spectral features. , In applying this method to estimate the relative WL chemical shifts of the spectra shown in Figure , the low energy integration limit, E L = 2516 eV (well below the edge) was used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure shows XANES measurements of the Mo-L 3 edges of LiMo 8 O 10 and a series of oxide standards with differing valances/configurations: MoO 3 (Mo 6+ , d 0 ), SrFe 0.5 Mo 0.5 O 3 (Mo 5+ , d 1 ), Sm 2 Mo 2 O 7 (Mo 4+ , d 2 ), MoO 2 (Mo 4+ , d 2 ), and elemental Mo (Mo 0 , d 5 ). The intense near-edge “white line” (WL) features in the spectra are due to dipole transitions from the 2p core level into empty 4d final states. The characteristic chemical shift of the absorption edge to higher energy with increasing valence can be seen in Figure by the systematic shift to the higher energy of the centrum of the WL feature with increasing Mo-valence. The loss of screening (an increase of binding energy) with increasing valence is typically invoked for such chemical shift trends . The strong splitting of the oxide spectra due to ligand field and band structure effects can complicate the evaluation of the WL chemical shift. The first moment of the near edge, E M , as defined in eq , has been used to estimate the relative chemical shifts of XANES spectra with strong spectral features. , In applying this method to estimate the relative WL chemical shifts of the spectra shown in Figure , the low energy integration limit, E L = 2516 eV (well below the edge) was used.…”
Section: Resultsmentioning
confidence: 99%
“…The intense near-edge “white line” (WL) features in the spectra are due to dipole transitions from the 2p core level into empty 4d final states. The characteristic chemical shift of the absorption edge to higher energy with increasing valence can be seen in Figure by the systematic shift to the higher energy of the centrum of the WL feature with increasing Mo-valence. The loss of screening (an increase of binding energy) with increasing valence is typically invoked for such chemical shift trends . The strong splitting of the oxide spectra due to ligand field and band structure effects can complicate the evaluation of the WL chemical shift. The first moment of the near edge, E M , as defined in eq , has been used to estimate the relative chemical shifts of XANES spectra with strong spectral features. , In applying this method to estimate the relative WL chemical shifts of the spectra shown in Figure , the low energy integration limit, E L = 2516 eV (well below the edge) was used. Following the analysis performed in the Re-containing compounds, the high energy limit was chosen as the energy where the postedge absorption coefficient fell below the absorption coefficient of μ = 1.5 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1991, Hämälainen et al demonstrated the dramatic sharpening of HERFD XAS technique on the L 3 edge of dysprosium, laying the foundation for the increasingly popular HERFD XAS approach. Today, the technique is being widely applied across the periodic table for a variety of elements, including the first, , second, and third row transition metals, main group elements, halogens, lanthanides, and actinides. …”
Section: X-ray Spectroscopic Methods and Recent Applicationsmentioning
confidence: 99%